A COMPREHENSIVE ANALYSIS OF THE FLORA OF CEMETERIES DISTRIBUTED IN THE CITY OF CHIRCHIK (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this article, the taxonomic composition of the flora of Muslim cemetery No. 2 is determined as a result of our field research conducted in 2022-2023. It has been established that the flora of this region consists of 33 families, 96 genera and 149 species. Taxonomic analysis of the grave flora, the number of taxa, families, species in percent. Spectra of polymorphic families and genera of plants, common in the cemeteries of the region, the natural flora of the cemeteries of the city of Chirchik and their significance are given.